A design method for optimizing the secondary reflector of a parabolic trough solar concentrator to achieve uniform heat flux distribution. (15th August 2021) - Tang, X.Y.; Yang, W.W.; Yang, Y.; Jiao, Y.H.; Zhang, T.
Abstract: Non-uniform solar flux distribution in a parabolic trough concentrator (PTC) causes large temperature gradients on absorber tube surface, making the PTC inefficient and damaged. To solve the problem, a novel method is proposed for designing the additional secondary reflector (SR) in a PTC to improve uniform heat flux distribution on absorber tube surface. In the design, the heat flux between upper and lower surfaces of absorber tube is well balanced by optimizing the location of absorber. Then, the SR with segmented broken-line type composed of multiple plane mirrors is delicately designed with local heat flux compensation strategy. Two case studies are conducted to compare the performances of the newly designed SRs with other existing SR designs. It is shown that the uniformity of heat flux distribution can be improved to over 90% for present SR design, much higher than those for other existing SR designs. Also, the optical efficiency of the PTC with present SR design is also increased as compared with other designs. The results indicate that this proposed method is competent for designing SR in a PTC with uniform heat flux distribution. Graphical abstract: Image 1 Highlights: A novel method is developed for designing the additional secondary reflector (SR) of PTCs. Flux compensation strategy is proposed by balancing the solar flux on upper and lower surfaces of absorber. Performances of PTCs with designed SR are compared with other studies and shows superior performance. The heat flux distribution on absorber is greatly enhanced and the uniformity exceeds 90%. High optical efficiency of PTC-SR can be achieved as compared with other SR designs.